2016
DOI: 10.1136/heartjnl-2016-309373
|View full text |Cite
|
Sign up to set email alerts
|

AdVEGF-B186and AdVEGF-DΔNΔCinduce angiogenesis and increase perfusion in porcine myocardium

Abstract: Both AdVEGF-B and AdVEGF-D gene transfers induced efficient angiogenesis in the myocardium resulting in an increased myocardial perfusion measured by PET. Importantly, local perfusion increase did not induce any coronary steal effect. As such, both treatments seem suitable new candidates for the induction of therapeutic angiogenesis for the treatment of refractory angina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…VEGF‐A165 and VEGF‐A121 both induce angiogenesis and increase blood flow. VEGF‐A165 is more highly expressed than VEGF‐A121, while VEGF‐A121 diffuses more into the ischemic milieu than VEGF‐A165; VEGF‐C and VEGF‐D stimulate lymphatic vessel growth and do not directly stimulate inflammatory responses . This meta‐analysis showed that VEGF‐A165 gene transfer could decrease the risk of serious cardiac events and that VEGF‐A121 gene transfer could increase ΔLVEF, which indicated that VEGF‐A165 may have greater potential in the prognosis of CAD, and VEGF‐A121 may be more beneficial in improving cardiac function; while these results should be further investigated.…”
Section: Discussionmentioning
confidence: 85%
“…VEGF‐A165 and VEGF‐A121 both induce angiogenesis and increase blood flow. VEGF‐A165 is more highly expressed than VEGF‐A121, while VEGF‐A121 diffuses more into the ischemic milieu than VEGF‐A165; VEGF‐C and VEGF‐D stimulate lymphatic vessel growth and do not directly stimulate inflammatory responses . This meta‐analysis showed that VEGF‐A165 gene transfer could decrease the risk of serious cardiac events and that VEGF‐A121 gene transfer could increase ΔLVEF, which indicated that VEGF‐A165 may have greater potential in the prognosis of CAD, and VEGF‐A121 may be more beneficial in improving cardiac function; while these results should be further investigated.…”
Section: Discussionmentioning
confidence: 85%
“…Induction of VEGF production in an endothelial cell culture has been found to promote cell division and cell proliferation [29]. Administration of VEGF genes into porcine myocardium induced angiogenesis and increase the microvascular bed about 1.8 folds as demonstrated by Nurro et al [30]. …”
Section: Discussionmentioning
confidence: 99%
“…Some studies have used PECAM-1 to estimate capillary density [39, 40]. In a recent study, diabetic rats were exposed to testosterone treatment and exercise training to investigate the effect on these two interventions on neoangiogenesis [30]. That study demonstrated higher PECAM-1 antibody staining after both treatment modalities were administered [41].…”
Section: Discussionmentioning
confidence: 99%
“…Both VEGF isoforms were able to increase myocardial perfusion, in particular under stressful conditions, as documented by positron emission tomography studies 1. The effects on perfusion were similar, although VEGF-D ΔNΔC was more potent than VEGF-B in generating copious and larger microvessels.…”
mentioning
confidence: 80%
“…The swine is considered a valuable organism system in translational medicine due to the similarities with the human organism (ie, size of the heart, type of myocardial perfusion and characteristics of excitation–contraction coupling system). In a recent Heart publication, Nurro et al 1 report interesting novel data on VEGF-B and VEGF-D isoforms gene therapy in a pig ischaemia and reperfusion model. Gene transfer was performed using adenoviral vectors carrying the VEGF-B 186 isoform and the proteolitically processed mature form of VEGF-D, ΔNΔC (VEGF-D ΔNΔC ), via a fluoroscopically guided injection into the left ventricle wall of healthy pigs.…”
mentioning
confidence: 99%